Synthesis of (-)-hygromycin A: application of Mitsunobu glycosylation and tethered aminohydroxylation. - Donohoe, T; Flores, A; Bataille, C; Churruca, F (2009)
Key points in the synthesis of (-)-hygromycin A are the tethered aminohydroxylation reaction used to prepare the aminocyclitol unit and the choice of a bulky protecting group on the sugar unit to facilitate selective Mitsunobu glycosylation and also bestow kinetic stability upon an otherwise vulnerable proton. © 2009 Wiley-VCH Verlag GmbH and Co. KCaA.